2018
DOI: 10.31487/j.cor.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effecT of quercetin on protein expression CtBP1 and migration of hepatocellular carcinoma cell SMMC-7721

Xiaoling Zhang

Abstract: A B S T R A C TOur study aimed to investigate the potential role of quercetin in the migration of hepatocellular carcinoma cells, SMMC-7721, and its underlying mechanism. Cell monolayer scratching assay was performed to explore the role of quercetin in the migration ability of SMMC-7721 cells. Western Blot and immunofluorescence assay were conducted to detect the protein expression of transcriptional co-suppressor, CtBP1, and epithelial adhesion molecule, E-cadherin. The migration ability of SMMC-7721 cells wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…As inflammatory cytokines in the process of immune regulation can be secreted by a variety of cells, such as tumor cells, and induce the directional migration of immune cells, CXCL2 has been reported to play a complex and variable role in tumor progression, even in different cell lines within the same tumor [24,44]. Studies have shown that CXCL2 can enhance the proliferation and migration of SMMC7721 hepatoma cells [45].…”
Section: Discussionmentioning
confidence: 99%
“…As inflammatory cytokines in the process of immune regulation can be secreted by a variety of cells, such as tumor cells, and induce the directional migration of immune cells, CXCL2 has been reported to play a complex and variable role in tumor progression, even in different cell lines within the same tumor [24,44]. Studies have shown that CXCL2 can enhance the proliferation and migration of SMMC7721 hepatoma cells [45].…”
Section: Discussionmentioning
confidence: 99%
“…Red raspberry (Rubus idaeusl L.) is an internationally popular third-generation fruit, which is rich in nutrients and contains anthocyanins, ellagic acid, salicylic acid, flavonoids and other active substances with anti-cancer [1], anti-aging [2], blood sugar [3] and lipid lowering effects [4,5]. Nitrogen fertilization is an important element that affects the yield of red raspberry [6].…”
Section: Introductionmentioning
confidence: 99%